Women, children and patience: experimental evidence from Indian villages - Michal Bauer; Julie Chytilová (Institute for the Study of Labor (IZA), 2009)
In this paper we study the link between women's responsibility for children and their preferences. We use a large random sample of individuals living in rural India, incentive compatible measures of patience and risk aversion, and detailed survey data. We find more patient choices among women who have a higher number of children. The age of children matters: The link with patience is specific for children below 18 years old, and the highest level of patience is associated with having three children. We do not observe this link among men. Taken together, we find significant gender differences in patience that are predicted by a higher number of children. The results are robust to controlling for age, education, income constraints, and individual and location characteristics. These findings suggest an important context when the spending preferences of spouses diverge, and support the view that empowering women in developing countries should lead to more future-oriented choices of households.
urn:nbn:de:101:1-2009070331
Keywords: C93; D13; D91; O12; 330; Time discounting; gender; children; experiment; India; Konsumentenverhalten; Zeitpräferenz; Risikoaversion; Frauen; Mütter; Kinderbetreuung; Ländlicher Raum; Test; Indien